Stabilization of Early Duchenne Cardiomyopathy With Aldosterone Inhibition: Results of the Multicenter AIDMD Trial - Raman, Subha V.; Hor, Kan N.; Mazur, Wojciech; Cardona, Andrea; He, Xin; Halnon, Nancy; Markham, Larry; Soslow, Jonathan H.; Puchalski, Michael D.; Auerbach, Scott R.; Truong, Uyen; Smart, Suzanne; et al. (Journal of the American Heart Association, 2019)
Background Duchenne muscular dystrophy incurs nearly universal dilated cardiomyopathy by the third decade of life, preceded by myocardial damage and impaired left ventricular strain by cardiac magnetic resonance. It has been shown that (1) mineralocorticoid receptor antagonist therapy with spironolactone attenuated damage while maintaining function when given early in a mouse model and (2) low-dose eplerenone stabilized left ventricular strain in boys with Duchenne muscular dystrophy and evident myocardial damage but preserved ejection fraction. We hypothesized that moderate-dose spironolactone versus eplerenone would provide similar cardioprotection in this first head-to-head randomized trial of available mineralocorticoid receptor antagonists, the AIDMD (Aldosterone Inhibition in Duchenne Muscular Dystrophy) trial. Methods and Results This was a multicenter, double-blind, randomized, noninferiority trial. Subjects were randomized to eplerenone, 50 mg, or spironolactone, 50 mg, orally once daily for 12 months. The primary outcome was change in left ventricular systolic strain at 12 months. Among 52 enrolled male subjects, aged 14 (interquartile range, 12-18) years, spironolactone was noninferior to eplerenone (∆strain, 0.4 [interquartile range, -0.4 to 0.6] versus 0.2 [interquartile range, -0.2 to 0.7]; =0.542). Renal and pulmonary function remained stable in both groups, and no subjects experienced serious hyperkalemia. Infrequent adverse events included gynecomastia in one subject in the spironolactone arm and facial rash in one subject in the eplerenone arm. Conclusions In boys with Duchenne muscular dystrophy and preserved left ventricular ejection fraction, spironolactone added to background therapy is noninferior to eplerenone in preserving contractile function. These findings support early mineralocorticoid receptor antagonist therapy as effective and safe in a genetic disease with high cardiomyopathy risk. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02354352.